Spatial Variability of Soil Physical and Chemical Properties in Akure, South Western, Nigeria (Global Journal of Science Frontier Research, 2017)
The determination of the spatial variability of soil physical and chemical properties enables essential requirement for crop growth and development. The objectives of the study therefore were to determine the soil physical and chemical properties and characterize the spatial variability of soil physical and chemical properties across the study area. The physical and chemical properties determined were bulk density, particle density, Soil Hydraulic Conductivity (SHC),Water Holding Capacity (WHC) and soil pH, Nitrogen (N), Phosphorus (P), Potassium (K), Calcium (Ca), Magnesium (Mg), Cation Exchange Capacity (CEC), Soil Organic Matter (SOM) respectively. The study was conducted at the Agricultural Engineering Research Farm land, the Federal University of Technology, Akure (FUTA). Soil samples were collected from three sampling depths between 0-60cm at an interval of 20cm at different 20 points across the field while coordinates of the soil sampling points were determined using Global Positioning System (GPS) procedures.
Keywords: soil property; GP S; sampling point; productivity potential